2002
DOI: 10.1074/jbc.m202066200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of c-Jun N-terminal Kinase in Oxidative Stress-mediated Suppression of Insulin Gene Expression

Abstract: Oxidative stress, which is found in pancreatic ␤-cells in the diabetic state, suppresses insulin gene transcription and secretion, but the signaling pathways involved in the ␤-cell dysfunction induced by oxidative stress remain unknown. In this study, subjecting rat islets to oxidative stress activates JNK, p38 MAPK, and protein kinase C, preceding the decrease of insulin gene expression. Adenovirus-mediated overexpression of dominantnegative type (DN) JNK, but not the p38 MAPK inhibitor SB203580 nor the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
230
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(239 citation statements)
references
References 79 publications
6
230
0
3
Order By: Relevance
“…Glucotoxicity and lipotoxicity are terms coined for the deleterious effects of high circulating concentrations of glucose and lipids, both at the level of insulin sensitivity and in beta cells. Chronically elevated glucose concentrations affect beta cell function and survival through increased generation of reactive oxygen species and mitochondrial dysfunction, endoplasmic reticulum (ER) stress, and JNK signalling [3][4][5]. NEFA, and in particular saturated NEFA, impair beta cell function and cause apoptosis through ceramide synthesis, JNK activation and oxidative and ER stress [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Glucotoxicity and lipotoxicity are terms coined for the deleterious effects of high circulating concentrations of glucose and lipids, both at the level of insulin sensitivity and in beta cells. Chronically elevated glucose concentrations affect beta cell function and survival through increased generation of reactive oxygen species and mitochondrial dysfunction, endoplasmic reticulum (ER) stress, and JNK signalling [3][4][5]. NEFA, and in particular saturated NEFA, impair beta cell function and cause apoptosis through ceramide synthesis, JNK activation and oxidative and ER stress [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress occurs in the diabetic state [8,38], and ROS are produced in islets through the non-enzymatic glycosylation reaction and the electron transport chain in mitochondria [12,39]. It was recently reported that p38 MAPK in isolated rat islets is activated by oxidative stress [40]. In our study, the active form of phospho-p38 was observed in the islets of diet-induced diabetic mice at the late stage of the high-fat diet, but the frequency of phospho-p38 was small compared with the percentage of SA beta-gal staining in the islets.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear accumulation of IPF1 was independent of glucose concentration and was evident at each of the 0.5, 5 and 25 mmol/l glucose conditions tested over 24 h. We and others have previously shown that stimuli such as glucose and glucagon-like peptide-1 (GLP-1) can promote the translocation of IPF1 from the cytoplasm to the nucleus in pancreatic beta cells [23,29,30]. Further studies have shown that nuclear export of IPF1 in response to oxidative stress is dependent on signalling events regulated through the activity of c-JNK [31]. Interestingly, thiazolidinediones have previously been shown to decrease oxidative stress [32] and to suppress c-fos/c-Jun [33].…”
Section: Discussionmentioning
confidence: 99%